Multilayer Coating Formation at the Deposition from Plasma; IOP Conference Series: Materials Science and Engineering; Vol. 116 : Advanced Materials and New Technologies in Modern Materials Science - Shanin S. A. Sergei Aleksandrovich (2016, 2016)
Title screen